Age Estimation with Smartphone: Is It Reliable for Forensics Identification? Estimasi Usia dengan Smartphone: Apakah Dapat Diandalkan dalam Identifkasi Forensik? - Ruth, Mieke Sylvia Margaretha Amiatun; Novita; Gita, Levina; Kurniawan, Arofi; Utomo, Haryono (TALENTA, 2020)
Age estimation is one of the important components in forensic science used for personal identification, biological profile reconstruction, and help narrowing the search possibilities. Age estimation can be done by various methods and biological evidence, such as the human face. The human face is one of biometrics that provides a variety of information.Â The purpose of this article is to evaluate the accuracy and reliability of age estimation with face using smartphone for forensic identification based on previous studies and experiences. Age estimation by face is based on age progression that causes attrition and degeneration on soft tissue. With the development of technology, age estimation by face can be done with applications or websites on smartphone. In general, the utilization of smartphone can reduce waste, pollution, research cost and easier to save and share. A lot of applications have been developed and free to download. Unfortunately, the accuracy of its results is unknown. In conclusion, the applications for age estimation on smartphone give quiet good results and can be used as a supporting tool to estimate age in forensic identification. Â